Job Resources and Work Engagement among Finnish Dairy Farmers. Issue 3 (3rd July 2018) - Kallioniemi, Marja K.; Kaseva, Janne; Lunner Kolstrup, Christina; Simola, Ahti; Kymäläinen, Hanna-Riitta
ABSTRACT: Objectives : The aims of this study were to examine job resources, work engagement and Finnish dairy farmers' preferences concerning methods to enhance overall well-being while working on farms. Methods : A postal survey yielded 265 completed questionnaires from 188 dairy farms. The sample was assessed as representative of Finnish dairy farmers. Exploratory factor analysis and a linear mixed model were utilized during the data analyzing process. Results : The variables lowering work engagement were stressors related to the workload and problems with health. Elevated work engagement was associated with the factors work with farm animals and family . The most important resource variables were "child or children, " "own family, " and "animal health." Female dairy farmers considered resource variables related to the family, love, and work with cattle as significantly more important than male dairy farmers. Male dairy farmers experienced higher work engagement and, concerning the dimensions, especially higher dedication and absorption than male respondents in a reference sample of workers in difference occupations. A sustainable farm economy and the possibility to have a holiday period were the most important methods to improve overall well-being on dairy farms. Conclusion : The results indicate that the family, working with cattle, healthy farm animals, a reasonable workload, and a sustainable farm economy have the capacity to create positive impacts on well-being among dairy farmers. Well-being on farms is a part of sustainable food production.